Bioremediation of hexavalent-chromium contaminated groundwater: Microcosm, column, and microbial diversity studies. (May 2022) - Lin, Wei-Han; Chen, Chien-Cheng; Ou, Jiun-Hau; Sheu, Yih-Terng; Hou, Deyi; Kao, Chih-Ming
Abstract: Sulfate reducing bacteria (SRB) have the capability of bioreducing hexavalent chromium [Cr(VI)] to trivalent chromium [Cr(III)] under sulfate-reducing conditions for toxicity reduction. However, a high amount of sulfate addition would cause elevated sulfide production, which could inhibit the growth of SRB and result in reduced Cr(VI) bioreduction efficiency. A slow release reagent, viscous carbon and sulfate-releasing colloidal substrates (VCSRCS), was prepared for a long-lasting carbon and sulfate supplement. In the column study, VCSRCS was injected into the column system to form a VCSRCS biobarrier for Cr(VI) containment and bioreduction. A complete Cr(VI) removal was observed via the adsorption and bioreduction mechanisms in the column with VCSRCS addition. Results from X-ray diffractometer analyses indicate that Cr(OH)3(s) and Cr2 O3(s) were detected in precipitates, indicating the occurrence of Cr(VI) reduction followed by Cr(III) precipitation. Results from the Fourier-transform infrared spectroscopy analyses show that cell deposits carried functional groups, which could adsorb Cr. Addition of VCSRCS caused increased populations of total bacteria and dsrA, which also enhanced Cr(VI) reduction. Microbial diversity results indicate that VCSRCS addition resulted in the growth of Cr(VI)-reducing bacteria including Exiguobacterium, Citrobacter, Aerococcus, and SRB. Results of this study will be helpful in developing an effective and green VCSRCS biobarrier for the bioremediation of Cr(VI)-polluted groundwater. Graphical abstract: Image 1 Highlights: Sulfate addition causes increased Cr(VI) bioreduction and SRB growth rates. VCSRCS is a slow-releasing and long-lasting substrate for sulfate/carbon supply. VCSRCS addition causes the growth of Cr(VI)-reducing bacteria and dsrA gene. Cr(OH)3 and Cr3 O2 are main forms of Cr(III) precipitates after Cr(VI) reduction. VCSRCS causes Cr(VI) removal via bioreduction and sorption mechanisms.